The importance of knowledge of fertile age couples regarding syphilis - Kadatua, Marwa H.; Nanlohy, Wildia; Corputty , Lintje Sintje; Latuamury, Sitti R (CV. Paperhome Indonesia, 2025)
Syphilis not only causes morbidity, but can also cause mortality for sufferers. In Indonesia, the Indonesian Ministry of Health (Kemenkes) reported that cases of syphilis or raja singa in Indonesia reached 20,783 cases in 2022. This figure increased by 70% compared to 2018 with 12,484 cases. Data from the Maluku Provincial Health Office in 2022 recorded the findings of 594 cases of sexually transmitted infections of Syphilis with an average productive age including mothers in the perinatal period and the majority of the distribution was in the city of Ambon. At the Suli Health Center, in 2023 when screening of pregnant women was carried out on the first visit, 193 mothers were found to have sexually transmitted infections of syphilis in 5 mothers, 2 of whom had given birth and had recovered, so that at the time of the study there were still 3 mothers in the perinatal period who were reactive to syphilis who were undergoing treatment. community service with the hope of providing knowledge to the public who are still unfamiliar with sexually transmitted diseases, especially in couples of childbearing age.